Comparison of 2 Fasciotomes for Treatment of Patients With Chronic Exertional Compartment Syndrome of the Anterior Leg. Issue 11 (29th November 2021) - de Bruijn, Johan A.; van Zantvoort, Aniek P.M.; Hundscheid, Henricus P.H.; Hoogeveen, Adwin R.; van Eerten, Percy; Teijink, Joep A.W.; Scheltinga, Marc R.
Background: Chronic exertional compartment syndrome (CECS) of the anterior leg compartment (ant-CECS) is frequently treated with a minimally invasive fasciotomy. Several operative techniques and operative devices exist, but none have been compared in a systematic and randomized manner. Purpose: To compare efficacy, safety, and postoperative pain of a novel operative device (FascioMax fasciotome) with a widely accepted device created by Due and Nordstrand (Due fasciotome) during a minimally invasive fasciotomy for ant-CECS. Study Design: Randomized controlled trial; Level of evidence, 2. Methods: Patients with bilateral isolated ant-CECS between October 2013 and April 2018 underwent a minimally invasive fasciotomy using the FascioMax fasciotome in 1 leg and the Due fasciotome in the contralateral leg in a single operative session. Symptom reduction at 3 to 6 months and >1 year, postoperative pain within the first 2 weeks, peri- and postoperative complications, and ability to regain sports were assessed using diaries, physical examination, and timed questionnaires. Results: Included in the study were 50 patients (66% female; median age, 22 years [range, 18-65 years]). No differences between the devices were found in terms of perioperative complications (both had none), minor postoperative complications including hematoma and superficial wound infection (overall complication rate: FascioMax, 8% vs Due, 6%), or reduction of CECS-associated symptoms at rest and during exercise. At long-term follow-up (>1 year), 82% of the patients were able to regain their desired type of sport, and 67% (33/49) were able to exercise at a level that was comparable with or higher than before their CECS-associated symptoms started. Conclusion: Both the FascioMax and the Due performed similarly in terms of efficacy, safety, and levels of pain within the first 2 weeks postoperatively. Registration: NL4274; Netherlands Trial Register.